2016
DOI: 10.1038/srep32010
|View full text |Cite
|
Sign up to set email alerts
|

Frobenius-norm-based measures of quantum coherence and asymmetry

Abstract: We formulate the Frobenius-norm-based measures for quantum coherence and asymmetry respectively. In contrast to the resource theory of coherence and asymmetry, we construct a natural measure of quantum coherence inspired from optical coherence theory while the group theoretical approach is employed to quantify the asymmetry of quantum states. Besides their simple structures and explicit physical meanings, we observe that these quantities are intimately related to the purity (or linear entropy) of the correspon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 84 publications
(217 reference statements)
2
41
0
Order By: Relevance
“…In fact, there exists a simple direct relationship between them C P (ρ) = (d − 1)C F (ρ), which indicates that the basis-independent quantity C F (ρ) can also be viewed as a renormalized measure of the maximal coherence contained in a given state. Intriguingly, we found that for d = 2 and 3, the formula of C P (ρ) coincides with that of O d , due to an equivalent expression of C F (ρ) [29] C F (ρ) = 1 2(d − 1)…”
Section: Discussionmentioning
confidence: 62%
“…In fact, there exists a simple direct relationship between them C P (ρ) = (d − 1)C F (ρ), which indicates that the basis-independent quantity C F (ρ) can also be viewed as a renormalized measure of the maximal coherence contained in a given state. Intriguingly, we found that for d = 2 and 3, the formula of C P (ρ) coincides with that of O d , due to an equivalent expression of C F (ρ) [29] C F (ρ) = 1 2(d − 1)…”
Section: Discussionmentioning
confidence: 62%
“…Recently, resource theory of asymmetry or reference frame has emerged which treats individual formulations of coherence measures as special cases [18][19][20][21][22][23][24]. It has been noted that both operational and geometric perspectives are in general significant for resource theory [15]- [17], [28], [45]. Since Frobenius-norm has a geometric perspective [46], the basis independent measure of coherence [28] employed here clearly has geometric interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…The invariance of the Frobenius norm under unitary transformation [28] leads to preservation of this basis independent measure of coherence for small uncertainty wave packets, since a pure basis rotation is unable to impact the value of coherence even for large boosts. So, if there are two parties Alice (O) and Bob (O Λ ) who do not share any reference frame, and suppose Alice possesses a single party state whose spread in momentum is narrow enough.…”
Section: Coherence Of a Spin-1/2 Particle With Gaussian Momentum mentioning
confidence: 99%
“…Based on the irreducible representation of the symmetry group and the Frobenius norm 22 , the SSD ranging from zero to unity is more capable to identify various nature of symmetries such as symmetry breaking, accidental degeneracy and spontaneous symmetry breaking 23 , in contrast to the previous explorations based on the abstract concepts of fuzz set 24 and transform information 25 . Recently, it was applied to the Frobenius norm-based measures for quantum coherence and asymmetry 26 .…”
Section: Introductionmentioning
confidence: 99%